A study on the efficiency of government spending, optimal fiscal policy and indigenous economic growth in Iran economy - Seyedkazemi, Mahdi; Zayandehroodi, Mohsen; Jalaee, Abdolmajid (International Journal of Contemporary Economics and Administrative Sciences, 2018)
The optimal combination of the government current and capital expenditures is very important from the aspect of influencing on the optimal economic growth, so that lack of attention to the type of government spending leads to inefficiency of the government fiscal policies and failure to achieve the high-valued objectives of economy. In the present study, we used the production function and considering efficiency of the government current and capital expenditures to evaluate their effects on the optimal economic growth. Then, we proposed appropriate policy recommendations. To this aim, we used the modified Devarajan’s model (1998) and vector error correction model for 1966-2013 time-series data. The results show that current and capital expenditures had respectively positive and negative effects on the optimal economic growth. In other words, in Iranian economy, current expenditures are more efficient than capital expenditures. This is in contradiction to the ideas about high efficiency of capital expenditures. The reason for this is the Iranian economy structure and the nature of government current and capital expenditures. So that capital expenditures despite accounting classification, have a non-development nature. This is because of low contribution of economic issues in capital expenditures and high contribution of economic issues in current expenditures. Moreover, due to non-flexibility of current expenditures over 70%, adopted current credits are allocated practically and only 10-30% of development credits are allocated. Selection of economic sectors for development expenditures is inefficient while, current expenditures leads to economic growth by creating real demand in the market.